Perancangan Business Continuity Plan dan Disaster Recovery Plan Teknologi dan Sistem Informasi Menggunakan ISO 22301 - Ito Setiawan; Retno Waluyo; Wahyu Aji Pambudi (Ikatan Ahli Informatika Indonesia (IAII), 2019)
Ananda Purwokerto Hospital already has system such as hospital information system (SIRUS), website and mobile application. but in the process of using information technology there are still many obstacles and prevention of problems that have not been well documented resulting in losses. This research is about design business continuity plan that functions to maintain the business continuity of the company so that it continues to run when information technology in the company is disrupted, where this study uses the 22301 international standard organization framework. This standard will greatly help the company in the process of develop business continuity plan with an identification methodology and analysis of the use information technology and the risks that will arise in the company. The evaluation results have not yet implemented the overall business continuity plan and many employees have not yet realized the importance of business continuity plan in the use of information technology. From the analysis, it turns out that there is no business continuity plan process implemented so that business continuity plan is designed that refers to international standard organization 22301, cluase 4: context of organization, cluase 5: leadership, cluase 6: planning, clause 7: support.